Protein-energy wasting and asymmetric dimethylarginine in peritoneal dialysis patients - Heleniak, Zbigniew; Małgorzewicz, Sylwia; Lichodziejewska-Niemierko, Monika; Rutkowski, Rutkowski; Aleksandrowicz-Wrona, Ewa; Dębska-Ślizień, Alicja (Acta biochimica Polonica, 2018)
Cardiovascular (CVS) morbidity and mortality in the peritoneal dialysis patients (PD) is 10-30-fold higher than in the general population. A relatively low level of adiponectin and a higher level of leptin are important predictors of vascular complications as well as CVS events in PD patients. The asymmetric dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthase, is an important risk factor of CVS morbidity and mortality. It is very important to establish all CVS risk factors in the PD patients to prevent CVS morbidity and mortality in this population. The aim of the study was to determine the plasma concentration of ADMA and adipokines in relation to the protein-energy wasting (PEW) in PD patients.The study was performed in 30 PD patients and in the control group which consisted of 23 healthy volunteers. Plasma levels of hsC-reactive protein, TNF, IL-6, leptin, adiponectin, oxyLDL and ADMA were measured by ELISA method in both groups. The nutritional status was determined by measuring the albumin, body mass index (BMI), the percentage of body fat (%F), lean body mass (LBM) and Subjective Global Assessment Score (SGA). The adequacy of dialysis was estimated by weekly Kt/V. In all PD patients, significantly higher levels of ADMA, leptin, oxyLDL, hsCRP and TNF in comparison to controls were observed. In contrast to well-nourished subjects, patients with PEW, in addition to increased hsCRP, showed significantly higher ADMA. PEW was associated with high levels of ADMA and hsCRP and this could probably be responsible for increased CVS risk in PD patients. The aim of the study was to determine the plasma concentration  of ADMA and adipokines  in the  relation to the protein – energy  wasting  (PEW) in PD patients. The study was performed in 30  PD   and in the control group consisted of 23 healthy volunteers . Plasma levels of  hsC-reactive protein, TNF, IL-6, leptin,  adiponectin, oxyLDL and  ADMA were measured by ELISA methods in  both groups. The assessment of nutritional status was determined by the  albumin, body mass index (BMI), percentage of body fat (%F), lean body mass (LBM) and Subjective Global Assessment Score (SGA).The adequacy of dialysis was estimated by  weekly Kt/V. In all PD patients, significantly higher levels of ADMA, leptin, oxyLDL, hsCRP and TNF in comparison to controls were observed. In contrast to well-nourished subjects,  patients with PEW, in addition to increased hsCRP, showed significantly higher ADMA. PEW was  associated with high levels of ADMA and hsCRP and this could probably be  responsible for increased CVS risk in PD patients.